ACTIVE PARTICIPATION OF KHOREZM WOMEN IN ASSISTANCE TO THE FRONT (TAMADDUN NURI JURNALI, 2025)
The article highlights the active participation of Khorezm women in providing assistance to the front, their activities in the agricultural sector during World War II, their contribution to providing the front with food and creating a defense fund, and the courage of women from the region in the army on the move, based on archival materials.